Analysing the Impact of Risk on Consumer Trust in Digital Banking Transformation - Lewalkar, Ashish (Digital Repository of Theses, 2026)
This study looks into how consumer trust and intention to continue using digital banking are affected by risk-related issues. Customers are becoming more vulnerable to cybersecurity risks, privacy violations, and perceived service uncertainty as a result of the banking industry's rapid digital transformation. The purpose of this study is to investigate the relationship between consumers' inclination to stick with digital banking services and their level of awareness of security assaults, perceived risk, security and privacy concerns, age, and online banking experience. Primary data were collected through self-administered questionnaire, and 387 valuable and usable responses were recorded. The analysis was conducted using SmartPLS 4 software, the data were analysed using the partial least square structural equation modelling (PLS-SEM) approach. According to the study's findings, digital trust is perceived as being effectively managed rather than just the absence of risks. When banks uphold open communication, strong security, and privacy policies, informed consumers show greater trust and loyalty. These results offer tactical guidance for initiatives aimed at retaining customers in digital banking. The study theoretically extends the knowledge of consumer behaviour in emerging field of digital banking and practically, it will help banking section adoption of digital infrastructure to understand the need of the consumer. Keywords: Consumer Trust, Digital Banking, Banking Industry, Cybersecurity Risks, Privacy Violations, Digital Transformation.